Assessment of Energy Efficiency and Conservation Aspects Based on Building Information Modeling at Park Residence Building - Faridah, Yunita Hasna; Girsang, Hamonangan (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
To save energy, according to two aspects of the Sustainable Development Goals (SDGs), namely Sustainable Urban Development (SDG 11) and Climate Change (SDG 13), concrete efforts that can be made are increasing energy efficiency and conservation, reducing greenhouse gas emissions, and strengthening resource sustainability. One of the initial efforts that can be made to increase energy efficiency and conservation is by applying Building Information Modeling (BIM) for energy simulation in building structures. One of the BIM-supporting software that can be used in energy simulations is Autodesk Revit, which functions for architectural, structural, mechanical, electrical, and plumbing (MEP) modeling, and Autodesk Green Building Studio, which is a cloud-based media for conducting simple simulations of building performance so that various aspects of its energy can be analyzed for assessment. The Green Building aspect assessment of GBCI used is the GREENSHIP Existing Building Ver1.1 parameter, taken from the Energy Efficiency and Conservation (EEC) aspect, which is a quantitative assessment and can be modeled. The results of the EEC aspect assessment using a quantitative assessment tool obtained a value of 5 points from a total maximum value of 28 points. This value indicates that the 1 Park Residence Building is a building that has not implemented Green Building and requires actions that support the sustainability aspect of the building.